(untitled) (Dermatology Reports, 2025)
Epidermolysis bullosa (EB) refers to a group of inherited disorders characterized by skin and mucous membrane fragility. This report presents the case of a 61-year-old Italian male with a localized variant of junctional epidermolysis bullosa (JEB) linked to the R795X mutation in the COL17A1 gene. The patient presented with bullous lesions, erosions, scars, and pigmentary changes on the pretibial areas and dystrophic nails. Genetic analysis confirmed the presence of the COL17A1 variant p.Arg795Ter (R795X) mutation, establishing a rare, localized variant of JEB. This case underscores the criticality of early and accurate diagnosis in the management of rare genetic disorders, as misdiagnosis can lead to ineffective treatments.